2004
DOI: 10.4315/0362-028x-67.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Distributions Describing Microbial Quality of Surfaces and Foods in Food Service Operations

Abstract: Data on the microbial quality of food service kitchen surfaces and ready-to-eat foods were collected over a period of 10 years in Rutgers University dining halls. Surface bacterial counts, total aerobic plate counts, and total and fecal coliform counts were determined using standard methods. Analysis was performed on foods tested more than 50 times (primarily lunch meats and deli salads) and on surfaces tested more than 500 times (36 different surfaces types, including pastry brushes, cutting boards, and count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…In another study, Sneed et al (49) proposed a standard for food contact surfaces of less than 20 CFU/cm 2 for MAB and less than 10 CFU/cm 2 for Enterobacteriaceae. These authors reported high levels of MAB on durable resin cutting boards (.20 CFU/cm 2 ), similar to those found in our study at facilities B, D, and E. Other researchers (35) reported lower average levels for MAB in cutting boards (10.16 CFU/4 cm 2 ), but 6.7% of samples analyzed had levels above 50 CFU/4 cm 2 . Microorganisms can become lodged in cracks and crevices of cutting boards that are not properly sanitized (53), and the humidity of cutting boards may favor detachment of bacteria from these food contact surfaces when they are swab sampled, enhancing bacterial recovery (32).…”
Section: Assessment Of Microbiological Safety and Qualitysupporting
confidence: 92%
“…In another study, Sneed et al (49) proposed a standard for food contact surfaces of less than 20 CFU/cm 2 for MAB and less than 10 CFU/cm 2 for Enterobacteriaceae. These authors reported high levels of MAB on durable resin cutting boards (.20 CFU/cm 2 ), similar to those found in our study at facilities B, D, and E. Other researchers (35) reported lower average levels for MAB in cutting boards (10.16 CFU/4 cm 2 ), but 6.7% of samples analyzed had levels above 50 CFU/4 cm 2 . Microorganisms can become lodged in cracks and crevices of cutting boards that are not properly sanitized (53), and the humidity of cutting boards may favor detachment of bacteria from these food contact surfaces when they are swab sampled, enhancing bacterial recovery (32).…”
Section: Assessment Of Microbiological Safety and Qualitysupporting
confidence: 92%
“…Food operation environments have major effects on the microbial contam ination of final food products (7,36), but most previous studies have been concerned with commercially manufac tured and prepacked products sold in retail markets or with RTE foods from street vendors (11,14,17,27,28,39). The present study was conducted to evaluate the microbiological quality of sandwiches prepared on site and served in bakeries, cafes, and sandwich bars.…”
Section: Discussionmentioning
confidence: 99%
“…If the dose at the point of consumption is assumed to fit a parametric distribution, then predictive Monte Carlo models can be avoided. While the appropriateness of any parametric distribution must be assessed on a case‐by‐case basis, numerous studies have demonstrated theoretically and empirically that it is reasonable to assume that microbial counts vary according to a lognormal ( 20,31‐33 ) or Poisson‐lognormal distribution. ( 34 ) Furthermore, the lognormal distribution is mathematically convenient and appropriate for modeling the effects of cooking, ( 34 ) growth, ( 35 ) and cross‐contamination.…”
Section: Modeling Of Consumed Dosementioning
confidence: 99%